2020
DOI: 10.1038/s41390-020-0777-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and predictive value of Doppler ultrasound for evaluation of the brain circulation in preterm infants: a systematic review

Abstract: Cools 1 on behalf of the eurUS.brain group INTRODUCTION: Very and extremely preterm infants frequently have brain injury-related long-term neurodevelopmental problems. Altered perfusion, for example, seen in the context of a hemodynamically significant patent ductus arteriosus (PDA), has been linked to injury of the immature brain. However, a direct relation with outcome has not been reviewed systematically. METHODS: A systematic review was conducted to provide an overview of the value of different cerebral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 83 publications
(104 reference statements)
0
21
0
2
Order By: Relevance
“…However, there is no clear evidence to support the routine determination of resistance index or other Doppler parameters in the cerebral arteries to predict IVH in preterm infants. 12,13 For the above reasons, we pay attention performing venous Doppler measurements instead of arterial ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear evidence to support the routine determination of resistance index or other Doppler parameters in the cerebral arteries to predict IVH in preterm infants. 12,13 For the above reasons, we pay attention performing venous Doppler measurements instead of arterial ones.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found no clear evidence for using single Doppler-derived parameters to predict neurological outcome in premature infants, although some evidence relates elevated RI in cerebral arteries to a hemodynamically significant ductus arteriosus (DA). 39 We did not assess the state of the DA at the time of testing. Spontaneous closure of DA is associated with decreased PI and increased systolic and diastolic BFV in both the anterior and middle cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the increased angle of insonation in premature newborns, when evaluating the descending aorta in the subcostal window, compared to a term newborn where one may have more amplitude of manipulation of the probe. During Doppler acquisition, angle of insonation between the sampled vessel and the ultrasound beam must be minimized to avoid imprecision in estimating the Doppler shift [ 18 , 19 ]. As such, the beam should interrogate the corresponding flow in a parallel fashion, as much as feasible [ 20 ].…”
Section: Discussionmentioning
confidence: 99%